Circulatory Responses to Operative Stress in Females with Gestosis - I. V. Mikhno (Общая реаниматология)
Objective: to study the specific features of hemodynamic responses in females with gestosis in the perioperative period; to evaluate the impact of intensive care on the basis of co-administration of dalargin, dexamethasone, pen-toxifylline, and reamberin.Materials and methods. A Diamant KM-AP-01 rheograph (Saint Petersburg) was used to study hemodynamic parameters in 142 patients in whom surgical delivery was made under spinal anesthesia. A control group comprised 30 patients with uncomplicated pregnancy; Group 1 included 26 females with moderate gestosis; Group 2 consisted of 27 females with moderate gestosis who received the developed intensive care regimen; Group 3 comprised 29 females with severe gestosis; Group 4 included 30 females to whom the developed intensive care regimen was applied on the basis of the concurrent use of dalargin, dexamethasone, pentoxifylline, and reamberin.Results: A neurogenic mechanism prevails in females with moderate gestosis. The decreased baseline cardiac index is mostly due to a high postload. Surgical stress does not deteriorate postoperative circulatory parameters, which suggests that females with moderate gestosis have adequate capacities for self-regulation. As gestosis progresses to a severe degree, a role of humoral mechanisms increases in the maintenance of arteriolar spasm. Arteriolar spasm and hypokinetic hemodynamics are retained within 5 postoperative days, which is indicative of the inadequacy of self-regulation and compensatory mechanisms in overcoming two stressors: severe gestosis and surgical aggression.Conclusion: the intensive care regimen developed on the basis of combined use of dalargin, dexamethasone, pentoxifylline, and reamberin favors a more intensive (the promptest) normalization of circulatory parameters after surgical delivery in females with moderate and severe gestosis.